The Ecology of bacterial communities in Amazonian floodplain lakes - Melo, Michaela Ladeira de (Universidade Federal de São Carlos, 2019)
The bacterioplankton plays a key role in the functioning of aquatic ecosystems and biogeochemical cycles. Despite of the growing interest in studying the ecology of such microorganisms, little is known about how bacterial communities are assembly and which factors regulate their composition and activity, especially in highly dynamic hydrological networks such as the Amazonian floodplains. Using optical properties within dissolved organic matter (DOM), we performed a characterization of the source, quantity and composition of DOM, the main energetic substrate for bacterioplankton. Applying high-throughput sequencing techniques, we also characterized the bacterial community composition (BCC) in different habitats and seasons of the annual hydrological cycle (flood pulse) in Amazonian floodplain lakes (Janauacá and Curuaí), and investigated the role of local filters and regional drivers in shaping these communities. Our results demonstrated a strong seasonal pattern in the environmental conditions, BCC, and DOM. Dispersal processes were important factors in shaping BCC, being affected by the connection and lateral exchange between the main river channel and its floodplains. In addition, the seasonal changes in the lake's environmental conditions were determinant for the successful establishment of dispersing bacteria. We also found a strong coupling between DOM and BCC, highlighting the important role of a small fraction of autochthonous labile DOM and its rapid turnover by bacterioplankton as an important process that keeps the DOM quantity relatively low and stable over the year. Additionally, we observed that bacteria interaction networks had an organized structure and that there were key species present in both floodplain lakes. We developed a network-based score (K-value) to identify these bacterial taxa, which play a crucial role in maintaining the structure and diversity of their ecological communities and in the functioning of their ecosystems. To the best of our knowledge, this was the first in-depth study of a BCC in the world's largest river basin, and demonstrated that the flood pulse modulates several regional and local drivers, which regulate microbial community structure and composition, that could ultimately impact regional carbon budgets and biogeochemical cycles.
Keywords: Bacterioplâncton; Composição da comunidade bacteriana; Matéria orgânica dissolvida; Várzeas amazônicas; Pulso de inundação; Bacterioplankton; Bacterial community composition; Dissolved organic matter; Amazonian floodplains; Flood pulse; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS